Atlantic families lives and letters in the later eighteenth century - Pearsall, Sarah M. S. (Oxford University Press, 2008)
The growth of the Atlantic world led to the separation of many families. Sarah Pearsall explores the lives and letters of these families, revealing the sometimes shocking stories of those divided by sea.